EFEK STOKASTIK RADIASI SINAR-X DENTAL PADA IBU HAMIL DAN JANIN - Niluh Ringga Woroprobosari (ODONTO : Dental Journal, 2016)
Background: Dental radiographic examination is one of the most frequent radiological examinations carried out. X-rays in dental radiography is a shortwave electromagnetic rays that cause ionization reaction to any biological material in its path. The purpose of this article is to give an overview of stochastic effects in general as well as to pregnant women and fetuses in particular.Discussion: Ionizing radiation, such as X-ray radiation, is potentially teratogenic. Safe dose has not been well defined, although there has been approved dosing limits. Gestational age most vulnerable is the end of week 2 to A weeks post-conception. If the much needed radiographs of a woman who is pregnant, then the X-ray exposure will be directed mostly to the head and neck area.Conc/usion: Therefore, the application of the principle of ALARA (As Low As Reasonably Achievable) as well as good protection, including instrument control, protection of the room, the cumulative exposure dose control, and the use of apron throughout the process, is noteworthy. Such protection, especially for pregnant women and fetuses.